Prūsų kalbos pirminių vardažodžių morfemų akcentinė galia - Rinkevičius, Vytautas (Baltistica, 2006)
THE ACCENTUAL POWER OF OLD PRUSSIAN PRIMARY NOMINAL MORPHEMES The article presents the first attempt to describe the Old Prussian accentuation system based on the main principles of morphological accentology. It aims to distinguish accentual properties of morphemes that determine the placement of stress in primary (non-derived) Old Prussian nouns. At least one accentual property of morphemes (roots and inflexions), i.e. accentual power (strong vs. weak), could be distinguished. Strong root morphemes are roots that remain stressed in all forms of a paradigm, while the weak ones are those that lack stress in at least one form. Thus nouns with strong roots (eg. grīkai, kaulei, crixtiānimans, rūkai, wijrai (wijrimans); kīrki, kurpi, mūti, rīki, tapali; most probably also uremmans, wirdemmans; also possibly kaāubri, strigli) belong to the constant stem-stress class, while nouns with weak roots (eg. gallū, gennāmans, mensā, mergūmans, widdewū; semmē; also possibly waikammans, kermenes) belong to the mobile stress class. Strong inflexional morphemes are those that are stressed in position after weak roots (eg. nom. sg. fem. -ā (-ū), -ē; nom. pl. masc. ai; dat. pl. -āmans (-ūmans), -amans), while the weak ones are never stressed (eg. acc. sg. -an, -in; -ans, -ins; also possibly nom. pl. of ā-, ē-, i-, u-stems, acc. pl. and dat. sg. of all flexional types and gen. sg. of ā-stem).